Shadows of Empire in West Africa
XXII, 368 p. 17 illus., 4 illus. in color.
Keywords: These essays reexamine European forts in West Africa as hubs where different peoples interacted, negotiated and transformed each other socially, politically, culturally, and economically. This collection brings together scholars of history, archaeology, cultural studies, and others to present a nuanced image of fortifications, showing that over time the functions and impacts of the buildings changed as the motives, missions, allegiances, and power dynamics in the region also changed. Focusing on the fortifications of Ghana, the authors discuss how these structures may be interpreted as connecting Ghanaian and West African histories to a multitude of global histories. They also enable greater understanding of the fortifications’ contemporary use as heritage sites, where the Afro-European experience is narrated through guided tours and museums.